1998
DOI: 10.1590/s0102-33061998000300005
|View full text |Cite
|
Sign up to set email alerts
|

Análise da estrutura de duas unidades fitofisionômicas de savana (cerrado) no sul do Brasil

Abstract: RESUMO -(Análise da estrutura de duas unidades fitorisionômicas de savana (cerrado) no sul do Brasil). A região de Jaguariaíva. situada no Estado do Paraná. sul do Brasil. abriga os últimos remanescentes de savana no Estado e pode ser considerada como marco do limite meridional de dislribuição deste lipo de vegetação no Brasil. O Parque Estadual do Cerrado (24"09' S; 50°18' WG) foi objeto deste estudo em que se analisou a estrutura da vegetação de duas formas fisionômicas de savana. o campo cerrado e o cerrado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
14

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
3
11
0
14
Order By: Relevance
“…Another possible reason would be their natural inexistence in these areas, a phenomenon favored by the fact they were more distant from forest matrices and waterways, and more isolated (Pagano et al, 1989). The non occurrence of forest species in savanna formations, even when close to waterways, could be caused by fires (Durigan et al, 1994;Uhlmann et al, 1998), and to stronger anthropic action, as it was found in Patrocínio (Felfili et al, 1993). An indication of the occurrence of plant species uncommon in savanna formations could be found in different works on cerrados, where the authors highlighted the exclusion of these species from their respective studies (Mantovani et al, 1985;Durigan et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Another possible reason would be their natural inexistence in these areas, a phenomenon favored by the fact they were more distant from forest matrices and waterways, and more isolated (Pagano et al, 1989). The non occurrence of forest species in savanna formations, even when close to waterways, could be caused by fires (Durigan et al, 1994;Uhlmann et al, 1998), and to stronger anthropic action, as it was found in Patrocínio (Felfili et al, 1993). An indication of the occurrence of plant species uncommon in savanna formations could be found in different works on cerrados, where the authors highlighted the exclusion of these species from their respective studies (Mantovani et al, 1985;Durigan et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…The number of species reported as peculiar to forest formations found in JBMB and in the locations used as a comparison could be higher since many species did not appear in the floristic reports used. (Ferracini et al, 1983) 27 0 0 ft cd Corumbataí, SP (Pagano et al, 1989) 96 0 0 f cd Moji-mirim, SP (Toledo Filho et al, 1989) 104 0 0 ft cd Itirapina, SP (Durigan et al, 1994) 44 0 0 ft cs Botucatu, SP (Bicudo et al, 1996) 58 1 (1,7) 1 f cd Agudos, SP (Paschoal and Montanholi, 1997) 67 3 (4,5) 2 f cs Franca, SP (Araújo et al, 1999) 65 2 (3,1) 2 f cd Assis, SP (Durigan et al, 1999) 154 1 (0,6) 1 f cs Assis, SP (Durigan et al, 1999) 192 5 (2,6) 4 f cd S.Rita Passa Quatro, SP (Batalha and Mantovani, 2001) 114 1 (1,0) 1 f cs S.Rita Passa Quatro, SP (Batalha and Mantovani, 2001) 82 1 (1,2) 0 f cd Brotas, SP (Durigan et al, 2001) 78 0 0 ft cs Jaguariaíva, PR (Uhlmann et al, 1998) 33 0 0 ft cs Águas Emendadas, DF (Felfili et al, 1993) 72 0 0 f cs Patrocínio, MG (Felfili et al, 1993) 68 0 0 f cd Uberlândia, MG (Costa and Araújo, 2001) 76 0 0 ft cs Uberlândia, MG (Costa and Araújo, 2001) 93 3 (3,2) 3 ft cd Água Boa, MT (Felfili et al, 2002) 80 0 0 f cs References: 1 -Rodrigues and Nave (2000); Felfili et al (2001);Silva Júnior et al (1998;.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A precipitação total do período de estudo, no posto de Jardim foi de 206,8mm (FUNCEME 2002) (Egler 1960;Takeuchi 1960;Rodrigues 1971;Dantas & Rodrigues 1982;Bastos 1984;Gottsberger & Moravetz 1986;Miranda 1993;Sanaiotti et al 1997), oito no Sudeste (O. Cavassan, dados não publicados; A.A.J.F. Castro, dados não publicados; Cesar et al 1988;Araújo et al 1997;Batalha & Mantovani 2000;Costa & Araújo 2001), sete no Centro-Oeste (Filgueiras 1990;Nascimento & Saddi 1992;Maury et al 1994), três no Nordeste (Figueiredo 1989;Oliveira-Filho & Carvalho 1993;Castro et al 1998) e um no Sul (Uhlmann 1998 Padrões fenológicos reprodutivos e síndromes de dispersão -As fenofases floração e frutificação foram determinadas com base no material botânico coletado. Quando este não foi coletado, fez-se anotações na caderneta de campo sobre presença da fenofase na espécie.…”
Section: Methodsunclassified
“…Difere também de áreas de cerrado s. s. do Paraná (H' = 2,78 nat.ind. -1 ) (Uhlmann et al 1998) (t = 9,05 e p < 0,009) e de Minas Gerais (H' = 2,9 nat.ind. -1 ) (Barreira et al 2002) (t = 11,17 e p < 0,009).…”
Section: Resultsunclassified